Análise dos movimentos de sentidos sobre valorização/desvalorização do trabalho dos(as) professores(as): quais pontes se têm atravessado? - Braido, Luiza da Silva (2021)
This study is part of the Research Line LP2 - Educational Public Policies, Educational Practices and their Interfaces of the Program and Graduate Studies in Education, at the Education Center, at the Federal University of Santa Maria. The objective was to investigate the meanings of valuing/devaluing the work of teachers, understood as pedagogical work, in educational public policies. The Analysis of Movements of Sense was chosen for the production and analysis of data. Through this analysis, the meanings that express appreciation were highlighted, and it was observed that devaluation is always intertwined with it. Therefore, it can be said that policies themselves often legalize the devaluation of teachers. The educational policies chosen to analyse the meanings were: a) Law of Guidelines and Bases of Education – nº 4.024/61. b) Law of Guidelines and Bases of Education - nº 5.692/71; c) Law of Guidelines and Bases of Education - nº 9.394/96; d) Fund for the Maintenance and Development of Elementary Education and the Valorization of Teaching – FUNDEF (1996); e) National Education Plan (2001 – 2011); f) Fund for the Maintenance and Development of Basic Education and the Valorization of Teaching – FUNDEB; g) Law No. 11.738, 2008 – National Professional Salary Floor Law; h) Decree No. 6.755, 2009 - National Training Policy; i) Resolution No. 5, 2010 - Guidelines for Career and Compensation Plans; j) National Education Plan (2014 - 2024); k) Decree No. 8,752, 2016 - Provides for the National Policy for Training Professionals in Basic Education; l) Law No. 13,415, 2017 Policy to Promote the Implementation of Full-Time High Schools; m) Fund for the Maintenance and Development of Basic Education and the Valorization of Education Professionals – FUNDEB (2020). It was found that public educational policies do not conceptualize what they call valorization. Thus, they only mention how this category is expressed, which represents an inconsistency, because the need to value teachers is perceived, however, this valuation is not defined. Likewise, when there is a need for valorization, it is because it is already undervalued, because, in capitalism, profit is valued, and this requires the intensification and overexploitation of workers as a whole. More than expressions, it is necessary to understand the movements and know how to work with them, therefore, applying them as enhancers of the pedagogical work carried out.